Comparação da hemossiderina com o tecnécio-99 na identificação do linfonodo sentinela do câncer de mama - Vasques, Paulo Henrique Diógenes (2016)
Introduction and objective: Sentinel Lymph Node Biopsy (SLNB) has currently replaced axillary dissection in early-stage breast cancer in clinically tumor-free patients. Technetium-99 (99Tc) is the gold standard for the identification of Breast Sentinel Lymph Node (SLN). Blue dyes are a less expensive and widely used option in Brazil. These dyes are responsible for several adverse and hypersensitivity reactions that – although rare – can put patients’ lives at risk. There is an interest in the discovery of new equivalent substances with less side effects than those used in SLNB. This research assesses the safety and equivalence of the use of hemosiderin in SLNB in breast cancer compared to technetium-99 (99Tc). Hemosiderin is a hemoglobin derivate identified in a preclinical trial that has proven to be effective in the SLNB of female dogs’ breasts. The aim of this research is to assess the safety and potential equivalence of the use of hemosiderin in SLNB in human breast compared to the 99Tc. Method: The experiments took place in the period from September 2011 to September 2013. Patients were selected from the Mastology Service of the MEAC/HC/UFC and included 14 volunteer women with breast cancer with primary tumors (T1/T2) and clinically tumor-free axilla who were submitted to SLNB using hemosiderin, produced based on an aseptic hemolysate obtained from autologous blood, injected in the periareolar region 24h before surgery on an outpatient basis. 0.5 mCi of 99Tc was also injected in the subareolar region in the immediate preoperative period. Patients underwent breast MRI and mammary scintigraphy. In the operating room, patients – under general anesthesia – were submitted to SLNB, with incision in the axillary fold guided by Gamma-Probe and dissection by planes until the identification of the point of maximum uptake of 99Tc, identifying the marked sentinel lymph nodes (SLN) and their colors. Breast procedure was defined based on the correlation of the size and location of primary tumor and the axilla procedure was performed based on the presence or not of SLN metastasis. All surgical specimens were sent for pathological and immunohistochemical study. Results: There were no side effects, allergic reactions, surgical infection or toxicity related to the method applied. The conocordance rate between hemosiderin and 99Tc was 100%. The sensitivity and accuracy of hemosiderin was 100%. An incidental finding refers to magnetic properties of axillary lymph nodes (ALN) identified as an hypersignal in the NMR with hemosiderin in 100% of the exams. In two of four cases with positive SLN on histopathology, the image of the NMR with hemosiderin suggested neoplastic involvement of the marked lymph node. Conclusion: Hemosiderin proved to be an efficient and safe dye that is equivalent to 99Tc in breast SLNB.